POSSIBLE IMPACT OF NCAM AND FGFR1 MOLECULE EXPRESSION PATTERNS ON THE BIOLOGICAL BEHAVIOR OF RENAL CELL CARCINOMA - Filipović , Isidora; Mioljević , Ana; Nikolić , Gorana; Filipović, Jelena; Radojević Škodrić, Sanja; Bogosavljević, Nikola; Zivotic , prof. dr Maja (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: The incidence of renal cell tumors (RCT) and the deaths caused by them has been increasing in recent decades. Although renal cell carcinomas (RCCs) represent only 2% of all cancers, these tumors are among the top ten causes of death in Europe, when cancers are concerned.Aim: As it is known that the neural cell adhesion molecule (NCAM) and fibroblast growth factor receptor 1 (FGFR1) interact on the surface of the cell membrane and can also be expressed in other cellular localizations, we decided to examine the potential influence of different patterns of their co-expression on the clinical and pathological characteristics of renal tumors.Material and methods: A total of 100 renal tumors, diagnosed at the Institute of Pathology, Faculty of Medicine, University of Belgrade, were analyzed. Immunohistochemical analysis was performed on tissue microarray slides, using NCAM (1:50, clone123C3.D5) and FGFR1 (1:100, clone M19B2) antibodies. Clinical and pathohistological characteristics of renal tumors were examined in relation to the presence and localization of the co-expression of NCAM and FGFR1 molecules.Results: Co-expression of NCAM and FGFR1 molecules in renal tumors was observed in the cytoplasm and on the membrane, however, these patterns did not depend on the pathohistological type of tumor. Each tumor in which FGFR1 immunopositivity was observed in the nucleus also showed membranous positivity for both tested molecules. It was observed that the frequency of co-expression of NCAM and FGFR1 molecules increased with increasing T stage, but the finding was not statistically significant.Conclusion: Membranous co-expression was not observed in any benign tumor, despite the presence of cytoplasmic co-expression. There is also a possibility that the presence of FGFR in the nucleus induces the occurrence of membranous co-expression.
Keywords: RCT; RCC; neural cell adhesion molecule; NCAM; fibroblast growth factor receptor 1; FGFR1; renal tumors